AIR POLLUTION IN KRAKOW – A GLANCE INTO THE FUTURE FROM A HISTORICAL PERSPECTIVE - Wanda Wilczyńska-Michalik; Marek Michalik (Acta Geobalcanica, 2017)
High concentrations of air pollution probably occurred in Krakow in the nineteenth and early twentieth centuries. Since the late 1960s due to the development of monitoring networks level of air pollution is well documented. In the past few decades, a considerable drop in SO2 concentration has been observed in conjunction with a major increase in the particulate matter and nitrogen oxides concentrations. The complex composition of aerosol particle samples (quartz, feldspars, clay minerals, carbonates, sulphates, chlorides, aluminosilicate and iron or iron oxide spherules of industrial origin and soot) suggests the multiplicity of their sources. In the near future, increased concentration of very fine particles and precursors of photochemical smog should be expected because of increasing emission from vehicle engines.